Species composition dynamics for bark beetles and their predators from Coleptera family in pine stands of the Zhovtneve State Forest Enterprise (Kharkiv region) in 2019–2022 - Воробей , А. Д. (Forestry and Forest Melioration, 2022)
Introduction Recently, outbreaks of bark beetles Ips acuminatus (Gyllenhal, 1827) and Ips sexdentatus (B?rner, 1776) have been registered in the pine forests of many regions. In Ukraine, predatory insects played a significant role in decline of these outbreaks. In 2018, researchers of the State Specialized Forest Protection Enterprise (SSFPE) “Kharkivlisozahyst” started rearing the predatory insect Thanasimus formicarius (Linnaeus 1758) (Coleoptera: Cleridae). Reared predators were released in 2018–2019 into the forests of Sumy, Chernihiv, and Kharkiv regions. The effectiveness of the measure was evaluated by the change in the tree health condition and the population indices of bark beetles, which were determined by assessment under the bark of model trees in the areas where the predator was introduced, and in the control, where the predator was not introduced. The assessment of bark beetles and their predators was also carried out in traps to identify their species composition and population dynamics for individual predator species during the bark beetles outbreak. It is important for improving the biological method of forest protection by means of using natural enemies of bark beetles. The aim of the research was to identify the features of the three-year dynamics of the species composition of bark beetles and their coleopterous predators in the stands which are located within the same forestry but differ in both the tree species composition and the measures taken. Materials and Methods During 2020–2022, the species composition and distribution of bark beetles and their predators were assessed by means of window traps in three forest plots in the Babaivske Forestry of the Zhovtneve State Forest Enterprise (Kharkiv Region). In 2019, Thanasimus formicarius (Linnaeus 1758), which was reared at the SSFPE "Kharkivlisozakhyst", was introduced into the bark beetles focus at site B-1 in pure 70-year-old pine stands with a relative density of stocking 0.7 (fresh relatively fertile forest site conditions – B2). In plot B-2 with similar stand characteristics and in plot L with mainly deciduous species of the same age and relative density of stocking, but with curtains of Scots pine (Pinus sylvestris L.), the predator was not introduced. Results and Conclusions In the window traps, four species of bark beetles and ten species of coleopterous predators were found. The lowest number of bark beetles and the highest predator/bark beetle ratio was detected at site B-1. To the greatest extent, in all experimental plots and in all years, Th. formicarius and Platysoma elongatum (Leach, 1817) were presented. The proportion of Th. formicarius in predator complex only in 2020 was the largest in variant B-1 where it was additionally introduced in 2019. 5 Figs., 3 Tables, 19 Refs.